Karet Alam Sebagai Basis Pembangunan Pedesaan dan Peningkatan Tarap Hidup Masyarakat yang Berkelanjutan: Kritik Atas Paradigma Developmentalisme - Rijal Ramdani; Eko Priyo Purnomo; Retno Dewi Pramudya Ahsani (Jurnal Ilmu Pemerintahan Widya Praja, 2018)
ABSTRACTThe research argues that natural rubber plantation can become a main priority of development process in Indonesian rural regions. Even thought by four years the price of the commodity has been impressively decreasing, it does not relate with the quality and prosperity of farmer’s daily life. Moreover, the plantation has a sustainable characteristic as the commodity is adaptive with environmental biodiversity. This argument can be a point of view to criticize the paradigm of developmentalism focusing on the economic growth and industrialization. Besides, by using the paradigm of institutionalism, as the highest population of poor families concentrated in the rural region, it also argues that the main duty of current Indonesia government is how to stabilize the rubber price in the national market and how to develop a sustainable institution of rubber farmers. Qualitative method was adopted in the research when the primary and secondary data are collected through observation, documentation, and in-deep interview. The research was conducted in Bengkalis regency, Riau Province, and Garut regency, West Java.